A new der(1;7)(q10;p10) leading to a singular 1p loss in a case of glioblastoma with oligodendroglioma component. Issue 2 (30th September 2013) - Gadji, Macoura; Crous‐Tsanaclis, Ana‐Maria; Mathieu, David; Mai, Sabine; Fortin, David; Drouin, Régen
<x xml:space="preserve">Abstract</x> The combined 1p‐/19q‐ deletions in oligodendrogliomas originate from translocation between both chromosomes. In the few cases of oligoastrocytomas and glioblastomas with an oligodendroglioma component (GBMO) where only 1p deletion was described, the origin remains unknown. We report the first case of GBMO, in which a single 1p deletion was detected and was linked to a translocation between chromosomes 1 and 7. Fresh surgical specimens were collected during surgery and the samples were used for cell culture, touch preparation smear slides (TP slides) and DNA extraction. Peripheral venous blood was also collected from the patient. G‐banding using Trypsin and stained with Giemsa (GTG) banding and karyotyping were performed and 1p‐/19q‐, TP53, PTEN and c‐MYC were analyzed by fluorescent in situ hybridization (FISH). Multicolor FISH (mFISH) and microsatellites analyses were also performed to complete the investigation. Three‐dimensional quantitative FISH (3D‐QFISH) of telomeres was performed on nuclei from TP slides and analyzed using TeloViewTM to determine whether the 3D telomere profile as an assessment of telomere dysfunction and a characterization of genomic instability could predict the disease aggressiveness. An unbalanced chromosomal translocation was found in all metaphases and confirmed by mFISH. The karyotype of the case is: 50∼99, XXX, +der(1;7)(q10;p10), inc[47] The derivative chromosome was found in all 47 analyzed cells, but the number of derivatives varied from one to four. There was neither imbalance in copy number for genes TP53 and PTEN, nor amplification of c‐MYC gene. We did not find loss of heterozygosity with analysis of microsatellite markers for chromosomes 1p and 19q in tumor cells. The 3D‐telomere profile predicted a very poor prognostic and short‐term survival of the patient and highlights the potential clinical power of telomere signatures as a solid biomarker of GBMO. Furthermore, this translocation between chromosomes 1 and 7 led to a singular 1p deletion in this GBMO and may generate the 1p and 7q deletions.